National Notifiable Diseases Surveillance System, 1 January to 31 March 2014 - No authors listed (Communicable Diseases Intelligence, 2014)
The National Notifiable Diseases Surveillance System collates data from Australian states and territories. These data have been published on the Department of Health website and quarterly data are published in Communicable Diseases Intelligence. This page contains data for the reporting period 1 January to 31 March 2014.